Effect of Phosphogypsum Amendment on Chemical Properties of Sodic Soils at Different Incubation Periods. (24th May 2022) - Hasana, Haile; Beyene, Sheleme; Kifilu, Alemayehu; Kidanu, Selamyihun
Abstract : The application of phosphogypsum (PG) on sodic soils provides nutrients to the soil, reduces the toxic effect of Na +, and improves soil properties. Laboratory experiments were performed to evaluate the effects of PG on the chemical properties of sodic soils. The treatments were arranged in a completely randomized design with five replications. The treatments included 0% GR (control), 50% GR (28.18 g·kg −1 ), 100% GR (56.37 g·kg −1 ), 150% GR (84.50 g·kg −1 ), and 200% GR (112.74 g·kg −1 ) rates that were thoroughly mixed with soil under incubation, whereas PG was mixed with topsoil before leaching at the same application rates under the leaching experiment. Soil and leachate samples from each pot were collected in 7, 14, 21, 28, and 35 days and subjected to spectrometric analysis. Results indicated that there was a highly significant (p < 0.001 ) effect on soil pH, exchangeable sodium percentage (ESP), available P, exchangeable Na +, and Ca +2 under 35-day incubation compared with control. In a closed incubation system, most of the nutrients were released after 7 days of incubation and inconstantly released after 14 days of incubation. Furthermore, the removal of Na + and SAR increased in initial leachate collection and decreased with the subsequent application of irrigation water (PV). Because of the high contents of Ca +2 released from PG and the residual effect of H2 SO4, soil pH and ESP were rapidly reduced compared with control. Post leachate analysis also revealed that available P and extractable S-SO4 −2 were significantly (p < 0.001 ) increased in soil solutions. However, available P was decreased during incubations compared with the value of post leachate analysis. During a closed incubation, displaced Na + replaces Ca +2 on exchange sites, resulting in increased Ca-P precipitation. Thus, the combined application of PG and irrigation water in 7 to 14 days would allow chemical reaction with the soils and reduce sodicity problems to crop planting.